Perioperative screening, management, and surveillance of Barrett's esophagus in bariatric surgical patients. Issue 1 (13th August 2020) - Ooi, Geraldine J.; Browning, Alison; Hii, Michael W.; Read, Matthew
Abstract: Obesity is a strong risk factor for Barrett's esophagus (BE), the only proven precursor lesion to esophageal adenocarcinoma (EAC). Bariatric surgery is currently the only reliable treatment that achieves long‐term sustained weight loss; however, it can markedly affect the development of de novo BE, and the progression or regression of existing BE. Bariatric procedures may also have implications on future surgical management of any consequent EAC. In this review, we examine the current evidence and published guidelines for BE in bariatric surgery. Current screening practices before bariatric surgery vary substantially, with conflicting recommendations from bariatric societies. If diagnosed, the presence of BE may alter the type of bariatric procedure. A selective screening approach prevents unnecessary endoscopy; however, there is poor symptom correlation with disease. Studies suggest that sleeve gastrectomy predisposes patients to gastroesophageal reflux and de novo BE. Conversely, Roux‐en‐Y gastric bypass is associated with decreased reflux and potential improvement or resolution of BE. There are currently no guidelines addressing the surveillance for BE following bariatric surgery. BE is an important consideration in the management of bariatric surgical patients. Evidence‐based recommendations are required to guide procedure selection and postoperative surveillance.